Short-term changes of response indicators of ecosystem status in broadleaved forests in Tuscany (central Italy) (WATER AIR AND SOIL POLLUTION, 1999)
The status of different response indicators of forest condition were measured and assessed between 1995 and 1997 at 6 Permanent Monitoring Plots (PMPs) in Tuscany (central Italy), where beech, holm oak and Turkey oak are the most frequent tree species. Foliage transparency, leaf damage and crown dieback have changed significantly over the monitoring period. Leaf area, length of the current year shoots, and total leaf area changed as well, but only for Turkey oak. Changes were consistent between and within the plots. Different indices of plant diversity showed marked changes, apparently linked to natural dynamics within individual ecosystems. These rapid and contrasting fluctuations in the various indicators of forest ecosystem make it difficult to derive a synthesis about the general condition of ecosystems and - especially - about the effects of air pollution.

Morpho-anatomical aterations in leaves of Fagus sylvatica L. and Quercus ilex L. in different environmental stress condition (Chemosphere, 1998)
By means of anatomical and foliar structure observations, this paper examines the ecological behaviour of two different species of broadleaf (a mesophile one, beech, and a xerophile one, holm-oak), under different conditions of water supply. The purpose of this study was to evaluate their response in relation to possible climate changes. The results highlight certain similarities of behaviour (reduction of leaf surface, increased leaf thickness, increase of mechanical structures in xeric stands). The main difference between the two species lies in the tannins content, which increase in the epidermal cells (vacuoles and walls) only in beech trees in xeric conditions

The role of marine salt and surfactants in the decline of tyrrhenian coastal vegetation in Italy (Annales des Sciences Forestières, 1995)
The decline of coastal vegetation is a phenomenon affecting some areas of the Mediterranean region and Australia; it is due to the presence of surfactants in marine aerosols, a consequence of sea pollution by detergents. This paper gives some observations made at various sites along the Tyrrhenian coast in Italy. The authors show that the presence of surfactants in the environment correlates with the presence of sea salt, and that the impact of surfactants on vegetation is local and occurs in association with strong sea winds. The study of the synergistic effect of surfactants and sea salt on the crowns of trees exposed to aerosols suggests that the surfactant can cause direct damage, while the absorption of sea salt is enhanced by the presence of the surfactant only when exposure to aerosol is prolonged, or if it is administered in very high concentrations.

CROWN STRUCTURE MODIFICATIONS IN RELATION TO AIR-POLLUTION (LANDSCAPE AND URBAN PLANNING, 1993)
Analysis of crown structure and crown modifications plays a role of primary importance in surveys of `new types of forest damage', since it is a decisive parameter in assessing the health status of a tree. Several forms of ramification alterations have been described in central and northern European species (Norway spruce, beech, Durmast oak, English oak, birch). This study examines the situation in Tuscany and offers a description of the alterations found in the main species typical of the Mediterranean region (Turkey oak, pubescent oak, holm oak, stone pine). The article discusses the potential impact of these alterations on the most typical forest formations, the ones which characterize the Tuscan landscape, and it describes the modifications already under way.